The rationale for patient‐reported outcomes surveillance in cancer and a reproducible method for achieving it. Issue 3 (30th November 2015) - Smith, Tenbroeck G.; Castro, Kathleen M.; Troeschel, Alyssa N.; Arora, Neeraj K.; Lipscomb, Joseph; Jones, Shelton M.; Treiman, Katherine A.; Hobbs, Connie; McCabe, Ryan M.; Clauser, Steven B.
Abstract : Patient‐reported outcomes (PROs) measure quality of life, symptoms, patient functioning, and patient perceptions of care; they are essential for gaining a full understanding of cancer care and the impact of cancer on people's lives. Repeatedly captured facility‐level and/or population‐level PROs (PRO surveillance) could play an important role in quality monitoring and improvement, benchmarking, advocacy, policy making, and research. This article describes the rationale for PRO surveillance and the methods of the Patient Reported Outcomes Symptoms and Side Effects Study (PROSSES), which is the first PRO study to use the American College of Surgeons Commission on Cancer's Rapid Quality Reporting System to identify patients and manage study data flow. The American Cancer Society, the National Cancer Institute, the Commission on Cancer, and RTI International collaborated on PROSSES. PROSSES was conducted at 17 cancer programs that participated in the National Cancer Institute Community Cancer Centers Program among patients diagnosed with locoregional breast or colon cancer. The methods piloted in PROSSES were successful as demonstrated by high eligibility (93%) and response (61%) rates. Differences in clinical and demographic characteristics between respondents and nonrespondents were mostly negligible, with the exception that non‐white individuals were somewhat less likely to respond. These methods were consistent across cancer centers and reproducible over time. If repeated and expanded, they could provide PRO surveillance data from patients with cancer on a national scale. Cancer 2016;122:344–351. © 2015 American Cancer Society . Abstract : National patient‐reported outcomes surveillance data could improve understanding of cancer care and its impact on people's lives, and provide data to support quality monitoring and policy making. This article describes the rationale for patient‐reported outcomes surveillance and relevant methods from the Patient Reported Outcomes Symptoms and Side Effects Study (PROSSES). See also pages 000‐000.